2013
DOI: 10.1186/1687-1847-2013-303
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of a schistosomiasis model with delays

Abstract: In this work, a nonlinear deterministic model for schistosomiasis transmission including delays with two general incidence functions is considered. Rigourous mathematical analysis is done. We show that the stability of the disease-free equilibrium and the existence of an endemic equilibrium for the model are stated in terms of key thresholds parameters known as basic reproduction number R 0 . This study of the dynamic of the model is globally asymptotically stable if R 0 ≤ 1, and the unique endemic equilibrium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…18 This approach has been used also in previous studies on other schistosomiasis models. 23,24 We use a human population of size H ¼ 1000 individuals with a life expectancy of 70 yr (l H ¼ 4 Â 10 À5 /day). The life expectancy of adult parasites is 5 yr 19,25 (l P ¼ 5.5 Â 10 À4 /day).…”
Section: B Parameter Estimationmentioning
confidence: 99%
“…18 This approach has been used also in previous studies on other schistosomiasis models. 23,24 We use a human population of size H ¼ 1000 individuals with a life expectancy of 70 yr (l H ¼ 4 Â 10 À5 /day). The life expectancy of adult parasites is 5 yr 19,25 (l P ¼ 5.5 Â 10 À4 /day).…”
Section: B Parameter Estimationmentioning
confidence: 99%
“…As far as models of co-infection are concerned, we found only two studies (Okosun and Smith 2017;Mushayabasa and Bhunu 2011). While a couple of people devoted their works on mathematical models with delays or with periodic environment (Yingke et al 2017;Lin and Zhicheng 2014;Zhang et al 2014;Guiro et al 2013;Shan et al 2011;Yun and Yuanguo 2016;Wu and Feng 2002;Castillo-Chavez et al 2008), very few researchers investigated the spatial dynamics of schistosomiasis Milner and Zhao 2008;Mari et al 2017;Shan et al 2014), and optimal control models (Ding et al 2015;Shan et al 2011;Ding et al 2017). Since none of these above-mentioned existing works have taken into account the role of human behavior on schistosomiasis, we spare the reader of their respective findings, because we want to remain focus on that newly incorporated transmission feature of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Chiyaka & Garira [4] investigated the host-parasite dynamics of schistosomiasis, Ishikawa et al [12] and Gurarie et al [7] considered the effect of a mass treatment program with snail control, while Chiyaka et al [13] observed that treatment eliminates the mature worms and active macrophages over a period of time with declining T-cell immune responses in the human body. The importance of public awareness campaigns was examined by Guiro et al [14] and Yingke et al [15], where Guiro et al [14] used two general non-linear incidence functions and distributed delay. Diaby et al [16] carried out a stability analysis of schistosomiasis dynamics, while Musa et al [17] promoted the use of vaccination, and Ronoh et al [18] considered the impact of environmental transmission in humans.…”
Section: Introductionmentioning
confidence: 99%